Dairy products and inflammation: A review of the clinical evidence. Issue 12 (13th August 2017) - Bordoni, Alessandra; Danesi, Francesca; Dardevet, Dominique; Dupont, Didier; Fernandez, Aida S.; Gille, Doreen; Nunes dos Santos, Claudia; Pinto, Paula; Re, Roberta; Rémond, Didier; Shahar, Danit R.; Vergères, Guy
ABSTRACT: Inflammation is a major biological process regulating the interaction between organisms and the environment, including the diet. Because of the increase in chronic inflammatory diseases, and in light of the immune-regulatory properties of breastfeeding, the ability of dairy products to modulate inflammatory processes in humans is an important but unresolved issue. Here, we report a systematic review of 52 clinical trials investigating inflammatory markers in relation to the consumption of dairy products. An inflammatory score (IS) was defined to quantitatively evaluate this interaction. The IS was significantly positive for the entire data set, indicating an anti-inflammatory activity in humans. When the subjects were stratified according to their health status, the IS was strongly indicative of an anti-inflammatory activity in subjects with metabolic disorders and of a pro-inflammatory activity in subjects allergic to bovine milk. Stratifying the data by product categories associated both low-fat and high-fat products, as well as fermented products, with an anti-inflammatory activity. Remarkably, the literature is characterized by a large gap in knowledge on bioavailability of bioactive nutrients. Future research should thus better combine food and nutritional sciences to adequately follow the fate of these nutrients along the gastrointestinal and metabolic axes.